Forwards-backwards hand velocity induced by the upper trunk rotation in front crawl strokes and its association with the stroke frequency - Kudo, S.; Mastuda, Y.; Yanai, T.; Sakurai, Y. (Journal of Sports Sciences, 2021)
The aim of this study was to determine the contribution of the upper trunk rotation consisting of roll-pitch-yaw to hand velocity in the forwards-backwards direction during front crawl strokes and to investigate the association of forwards-backwards hand velocity induced by the upper trunk rotation with stroke frequencies. Fifteen skilled swimmers with retro-reflective markers performed front crawl strokes in a swimming pool where a motion capture system was set. Forwards-backwards hand velocity solely induced by the upper trunk rotation was determined during the performance. In the pull and push phases, 28% and 19% of the backward hand velocity was induced by the upper trunk rotation, respectively, while 19% of the forward hand velocity resulted from the upper trunk rotation in the recovery phase. The upper trunk rotation contributed to the forwards-backwards velocity as much as the elbow joint and was the second primary source of backward hand velocity in the pull phase. The forwards-backwards hand velocity created by the upper trunk rotation was associated with the stroke frequencies (r = 0.56, p < 0.05). The forwards-backwards hand velocity induced by the upper trunk would influence hand propulsion and stroke frequency so that a swimmer and coach should consider this performance-enhancing variable.